RO-MAN 2007 - The 16th IEEE International Symposium on Robot and Human Interactive Communication 2007
DOI: 10.1109/roman.2007.4415233
|View full text |Cite
|
Sign up to set email alerts
|

Human-Robot Interactions as a Cognitive Catalyst for the Learning of Behavioral Attractors

Abstract: Abstract-We address in this paper the problem of the autonomous online learning of a sensory-motor task, demonstrated by an operator guiding the robot. For the last decade, we have developed a vision-based architecture for mobile robot navigation. Our bio-inspired model of the navigation has already proved to achieve sensory-motor tasks in real time both in unknown indoor and outdoor environments. We propose to bootstrap the underlying PerAc architecture in order to control the sensori-motor learning. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…For instance, in [23], we presented place fields having a useful radius of about 25 m., which was almost the size of the environment. In [21], we shown that an outdoor loop of 200m requires the same computation load an indoor loop of less than 15 m. For navigation capabilities, it is first possible to associate each place-cell with a particular movement in order to create a behavioral attraction basin [19], [16], [20]. We have shown that this behavior could learned by means of an intuitive human-robot interaction in indoor as well as in outdoor environments [21].…”
Section: Place Recognition and Visual Navigationmentioning
confidence: 92%
See 3 more Smart Citations
“…For instance, in [23], we presented place fields having a useful radius of about 25 m., which was almost the size of the environment. In [21], we shown that an outdoor loop of 200m requires the same computation load an indoor loop of less than 15 m. For navigation capabilities, it is first possible to associate each place-cell with a particular movement in order to create a behavioral attraction basin [19], [16], [20]. We have shown that this behavior could learned by means of an intuitive human-robot interaction in indoor as well as in outdoor environments [21].…”
Section: Place Recognition and Visual Navigationmentioning
confidence: 92%
“…This section describes a mature and efficient model of prehippocampal visual place-cells, tested on several platforms to perform missions in open indoor and outdoor environments [19], [16], [20], [21]. One Our model of entorhinal place-cells is inspired from "what and where" functional theory of the cortical connectivity downstream the hippocampus [40].…”
Section: Place Recognition and Visual Navigationmentioning
confidence: 99%
See 2 more Smart Citations
“…One promising approach to construct such a metric is to use the demonstrations to impose constraints in a dynamical system [24,38,44]. Giovannangeli and Gaussier [35] use human-robot interaction to improve generalization when learning sensory-motor behaviors for homing and path following. In the described work, teaching by error correction (proscriptive learning), is shown to give superior generalization compared to a regular demonstration (prescriptive learning).…”
Section: Case 1 Corresponds To What Is Often Called Action-level Imitmentioning
confidence: 99%